Social occupational therapy with poor rural youth: actions in public school - Magno Nunes Farias; Lívia Celegati Pan; Roseli Esquerdo Lopes (Universidade Federal do Norte do Tocantins, 2023)
The aim of this study is to put on screen the experience of the performance of social occupational therapy with poor rural young people, in a public school in a city in the interior of Brazil. The intervention was carried out during 2019, through Workshops of Activities, Dynamics and Projects, having with guiding axis the references of social occupational therapy and Paulo Freire. The Workshops were configured as spaces and moments of coexistence, reflection and experimentation that was intended to foster interesting and safe for a dialogue around individual and collective issues. The praxis were directed to problematization of these questions posed by the subjects, having as reference challenges and potentialities related to their experiences, in the search for the promotion of reflection-action, awareness and ways to overcome situations-limits evidenced. This process and its results allow us to identify and reaffirm the contribution of social occupational therapy to ensure spaces in which young are interlocutors and protagonists, especially in school, elaborating with these subjects ways to expand their experiences of the youth condition in the field of projects for life, of everyday circulation, dealing with conflicts, exercising citizenship, cultural negotiation, etc.